2015
DOI: 10.1371/journal.pone.0129694
|View full text |Cite
|
Sign up to set email alerts
|

IFN-Gamma Inhibits JC Virus Replication in Glial Cells by Suppressing T-Antigen Expression

Abstract: ObjectivePatients undergoing immune modulatory therapies for the treatment of autoimmune diseases such as multiple sclerosis, and individuals with an impaired-immune system, most notably AIDS patients, are in the high risk group of developing progressive multifocal leukoencephalopathy (PML), an often lethal disease of the brain characterized by lytic infection of oligodendrocytes in the central nervous system (CNS) with JC virus (JCV). The immune system plays an important regulatory role in controlling JCV rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…At various post-exposure time points, cells were harvested, and total RNA was extracted with an RNA extraction kit (RNeasy, Qiagen) according to the manufacturer’s instructions. RT-PCR reactions were performed as described previously (De Simone et al, 2015). After treatment with DNase I, followed by phenol/chloroform extraction and EtOH precipitation, cDNAs were synthesized using M-MuLV reverse transcriptase.…”
Section: Methodsmentioning
confidence: 99%
“…At various post-exposure time points, cells were harvested, and total RNA was extracted with an RNA extraction kit (RNeasy, Qiagen) according to the manufacturer’s instructions. RT-PCR reactions were performed as described previously (De Simone et al, 2015). After treatment with DNase I, followed by phenol/chloroform extraction and EtOH precipitation, cDNAs were synthesized using M-MuLV reverse transcriptase.…”
Section: Methodsmentioning
confidence: 99%
“…Each IFN induces a distinct ISG profile that includes both shared and unique members (56,57). These ISG proteins can exert, among numerous other activities, antiviral actions that can target vulnerabilities at all stages of the viral life cycle, including entry, transcription, translation, genome replication, assembly, and egress (reviewed in reference 58), although the described effects of most reports have concluded that the inhibition is largely at the level of viral transcription and translation, including studies on the structurally related polyomaviruses (59,60). The identified effector molecules in these studies include RNA-dependent protein kinase (PKR), adenosine deaminase (ADAR), guanylate-binding proteins (GBP1 and GBP2), and nitric oxide synthetase (NOS), although in other instances the observed effects are unascribed (61)(62)(63)(64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…If indicated, the addition of NH 4 Cl was coincident with the addition of PsV to a final concentration of 20 mM. L2 was detected by Western blotting with the K5L2 antibody (47)(48)(49)(50)(51)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human peripheral blood mononuclear cells (PBMC) were isolated from the heparinized blood of buffy coats by Ficoll-Paque technique, induced with PMA and Ionomycin, and conditioned media from either uninduced or induced PBMCs were collected as described previously (De-Simone et al, 2015). Conditioned media were supplemented into growth media (50%) of primary human fetal glial (PHFG) cells transfected with reporter constructs or infected with JCV.…”
Section: Methodsmentioning
confidence: 99%